A study of rare-earth 3-(4-methylbenzoyl)-propanoate compounds as corrosion inhibitors for AS1020 mild steel in NaCl solutions. (December 2018) - Peng, Yu; Hughes, Anthony E.; Deacon, Glen B.; Junk, Peter C.; Hinton, Bruce R.W.; Forsyth, Maria; Mardel, James I.; Somers, Anthony E.
Highlights: Novel rare-earth carboxylate compounds as corrosion inhibitors have been evaluated. The yttrium 3-(4-methylbenzoyl)-propanoate acts as a mixed inhibitor after 24 h. EIS and circuit models were used to evaluate the corrosion inhibition performance. SEM/EDS shows a wide distribution of yttrium (Y) on the surface after immersion. Abstract: In this work two novel rare-earth (RE) 3-(4-methylbenzoyl)-propanoate (mbp) complexes (RE(mbp)3 ; RE = La, Y) have been investigated and compared with the well-researched inhibitor, lanthanum 4-hydroxycinnamate (La(4-OHcin)3 ), for AS1020 mild steel in 0.01 M NaCl solutions. The electrochemical results reveal a high corrosion inhibition performance of Y(mbp)3 which is attributed to the build-up of a protective surface film with a high level of corrosion resistance particularly after 24 h. Surface analyses indicate that the metal surface is protected during the immersion in Y(mbp)3 -inhibited solutions and the presence of Y is confirmed on the substrate surface.